Histerese térmica de sistemas magnéticos nanoestruturados - Silva, Maria das Graças Dias da (2010)
We report a theoretical investigation of thermal hysteresis in magnetic nanoelements. Thermal hysteresis originates in the existence of meta-stable states in temperature intervals which may be tuned by small values of the external magnetic field, and are controlled by the systems geometric dimensions as well as the composition. Two systems have been investigated. The first system is a trilayer consisting of one antiferromagnetic MnF2 film, exchange coupled with two Fe lms. At low temperatures the ferromagnetic layers are oriented in opposite directions. By heating in the presence of an external magnetic field, the Zeeman energy induces a gradual orientation of the ferromagnets with the external field and the nucleation of spin- op-like states in the antiferromagnetic layer, leading eventually, in temperatures close to the Neel temperature, to full alignment of the ferromagnetic films and the formation of frustrated exchange bonds in the center of the antiferromagnetic layer. By cooling down to low temperatures, the system follows a different sequence of states, due to the anisotropy barriers of both materials. The width of the thermal hysteresis loop depends on the thicknesses of the FM and AFM layers as well as on the strength of the external field. The second system consists in Fe and Permalloy ferromagnetic nanoelements exchange coupled to a NiO uncompensated substrate. In this case the thermal hysteresis originates in the modifications of the intrinsic magnetic